Double-ionization mechanisms of the argon dimer in intense laser fields - Ulrich, B.; Vredenborg, A.; Malakzadeh, A.; Meckel, M.; Cole, K.; Smolarski, M.; Chang, Z.; Jahnke, T.; Dörner, R. (My University, 2010)
We have measured the two-site double ionization of argon dimers by ultrashort laser pulses leading to fragmentation into two singly charged argon ions. Contrary to the expectations from a pure Coulomb explosion following rapid removal of one electron from each of the atoms, we find three distinct peaks in the kinetic energy release (KER) distribution. By measuring the angular distribution of the fragment ions and the vector momentum of one of the emitted electrons for circular and linear laser polarization, we are able to unravel the ionization mechanisms leading to the three features in the KER. The most abundant one results from tunnel ionization at one site followed by charge-enhanced tunnel ionization of the second atom. The second mechanism, which leads to a higher KER we identify as sequential tunnel ionization of both atoms accompanied by excitation. The third mechanism is present with linearly polarized light only. It is most likely a frustrated triple ionization, where the third electron does not escape but is trapped in a Rydberg state.